STRATEGI KOMUNIKASI POLITIK HERMAN ABDULLAH DAN AGUS WIDAYAT DIKOTA PEKANBARU PADA PEMILIHAN KEPALA DAERAH DI PROVINSI RIAU TAHUN 2013 - ", Harianto; Tinov, Tiyas (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
Communication stategy of local candidate is that the creation of efective and efficient communication between candidate and voters. In 2013 local election, candidate used many ideas to get people's vote. Some candidate spend a lot of money to get voted. Another candidate joint the election with people's blessing. People of pekanbaru city adore HERman abdullah due to his achievement in pekanbaru as major. Herman abdullah lead pekanbaru smoothly and the improvement of this city quite fast. Pekanbaru used to get ADIPURa award when he became rhe major. Education was his focus, espexially for the prosperity of guru madrasah ( teachers of Islamic school). Pekanbaru is known for the corruption free city in his era. Writer used communication strategy theory to find out politic communication strategy of herman Abdulah in PEkanbaru in 2013 local election.Writer used interview and documentation in collecting the data. This is a qualitative descriptive research. Writer entitled this research as Communication politic strategy of Hetman Abdullah and Agus Hidayat in Pekanbaru city in local election of Riau province 2013The success of Herman Abdullah in the election due to support from other political leader. Herman abdullah has a close relationship with some important figures in Pekanbaru. Herman Abdullah has a good leadership and positive image due to his success in some field before. Herman abdullah join the election by himself without any candidate for his spouse yet. It can be from anybody, since he didnt ask support from Golkar. Herman Abdulah has already communicate with PDIP, PKS, PBB, PPP, yet he will ask support from all people in society.Key word: strategy, politic communication, local election.